PROGRAM PENDAMPINGAN DAN PELATIHAN PENELITIAN TINDAKAN KELAS DENGAN MENERAPKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI SMPN 1 LUMPO - Yenni Melia; Erningsih; Yanti Sri Wahyuni; Sri Rahayu; Irwan; Elvawati (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
The focus of this study is to analyze the problem-based learning model that can be applied to students holistically or holistically. The method used in this study is data collection on program implementation, workshops to improve teacher pedagogic competence in implementing problem based learning models, mentoring in classroom action research training, building cooperative relationships between partners and the Education Office at the District and Provincial levels and evaluation. The results of the study show that the learning process still depends on concrete objects and experiences experienced directly. The first problem that arises is the teacher, the second problem is learning activities, and the third problem is learning resources and learning models. While the solution is that the teacher is able to find a learning model that matches the results of the research and observations made by the teacher at school. The preparations carried out include: preparation of learning, implementation of learning, and evaluation of learning processes and outcomes.